The Influence of Brand Image, Price, And Product Review on Product Purchase Interest in Lazada: Case Study on Lazada Users in Indonesia - Sonja Andarini; Akbar Tri Kurniawan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study aims to determine the effect of brand image, price, and product reviews on product repurchase intention in Lazada Indonesia. The population in this study are consumers who use Lazada Indonesia's e-commerce services who have made transaction purchases at least once. This study used a sample of 109 respondents. The sampling technique used was purposive sampling technique with the following criteria: (1) lazada Indonesian e-commerce service users are at least 17 years old, and (2) have made at least 1 purchase at dilazada.co.id. The data analysis technique uses the Multiple Linear Regression analysis method with IBM Statistic 22 software. The results of this study indicate that brand image has a positive and significant effect on repurchase intention, while the price variable has a positive and insignificant effect on repurchase intention. and product review variables have a negative and insignificant effect on repurchase intention.